Methods of test for boric acid, boric oxide, disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of sodium oxide, boric oxide and available oxygen contents of hydrated sodium perborates Part 4, (28th February 1979) - British Standards Institution,
No abstract available